PENGARUH TEKNIK RELAKSASI GENGGAM JARI TERHADAP PENURUNAN INTENSITAS NYERI PASIEN POST OPERASI FRAKTUR DI RUMAH SAKIT BHAYANGKARA MAKASSAR - Satriani, Andi Eka; Thahir, Nuryanti; Rosnia, Rosnia (Patria Artha University, 2022)
Pain after surgery is caused by mechanical stimulation of the wound which causes the body toproduce pain chemical mediators. Pain after fracture surgery will have an impact on the endocrinesystem which will increase the secretion of cortisol, catecholamines, and other stress hormones(Kurniawan, 2015). The finger grip relaxation technique is one of the non-pharmacological painmanagement methods that aims to reduce pain by holding fingers, inhaling, and diverting thepatient's attention to other things such as imagining a very pleasant event for the individual. Thus, itcan tolerate the pain that is felt. This study aims to determine the effect of finger grip relaxationtechniques in reducing the pain intensity of postoperative fracture patients, identifying pain intensitypre / post therapy, and analyzing the effect of finger grip relaxation techniques. The method used isQuasi Experimental with One Group Pre-Post Test Design. The sample size was 18 postoperativefracture patients who were hospitalized at Bhayangkara Hospital Makassar. The t test method with asignificance level of 0.05. The results showed the effect of finger grip relaxation techniques onreducing pain intensity. The results of this test also show that the provision of therapy before andafter with a value of t count 7,000 t table 2.109 with a value of ρ 0.000 α 0.05. It is hoped thatpostoperative fracture patients can apply what has been taught so as to reduce pain. Keywords: Post Operation Fracture, Pain, Finger Grip Relaxation Technique